Quantitative spectrofluorometric assay detecting nuclear condensation and fragmentation in intact cells - Majtnerova, Pavlina; Capek, Jan; Petira, Filip; Handl, Jiri; Rousar, Tomas (Scientific reports, 2021)
At present, nuclear condensation and fragmentation have been estimated also using Hoechst probes in fluorescence microscopy and flow cytometry. However, none of the methods used the Hoechst probes for quantitative spectrofluorometric assessment. Therefore, the aim of the present study was to develop a spectrofluorometric assay for detection of nuclear condensation and fragmentation in the intact cells. We used human hepatoma HepG2 and renal HK-2 cells cultured in 96-well plates treated with potent apoptotic inducers (i.e. cisplatin, staurosporine, camptothecin) for 6-48 h. Afterwards, the cells were incubated with Hoechst 33258 (2 µg/mL) and the increase of fluorescence after binding of the dye to DNA was measured. The developed spectrofluorometric assay was capable to detect nuclear changes caused by all tested apoptotic inducers. Then, we compared the outcomes of the spectrofluorometric assay with other methods detecting cell impairment and apoptosis (i.e. WST-1 and glutathione tests, TUNEL, DNA ladder, caspase activity, PARP-1 and JNKs expressions). We found that our developed spectrofluorometric assay provided results of the same sensitivity as the TUNEL assay but with the advantages of being fast processing, low-cost and a high throughput. Because nuclear condensation and fragmentation can be typical markers of cell death, especially in apoptosis, we suppose that the spectrofluorometric assay could become a routinely used method for characterizing cell death processes.
Keywords: buněčné jádro; buňky Hep G2; Bisbenzimidazole; kamptothecin; buněčná smrt; buněčné linie; cisplatina; Cisplatin; Humans; DNA Fragmentation; Cell Line; Antineoplastic Agents; Cell Nucleus; bisbenzimidazol; reprodukovatelnost výsledků; protinádorové látky; Staurosporine; Hep G2 Cells; apoptóza; Flow Cytometry; Cell Death; fragmentace DNA; průtoková cytometrie; Microscopy, Fluorescence; Spectrometry, Fluorescence; Camptothecin; staurosporin; lidé; Reproducibility of Results; Apoptosis; fluorescenční spektrometrie; fluorescenční mikroskopie